Improving Students’ Reading Comprehension through SQ3R : A Classroom Action Research - Nurul Kamila; Mustasyfa Thabib Kariadi; Laxmi Mustika Cakrawati (Jurnal Vokasia, 2024)
Reading was a fundamental language skill essential for acquiring knowledge, expanding vocabulary, and understanding textual information. This reading ability can be achieved with effective teaching, such as the SQ3R method that helps students more easily understand and remember the material. The aim of this research is (1) to describe the implementation of SQ3R (Survey, Question, Read, Recite, Review) method in teaching descriptive texts; (2) to find out whether the implementation of SQ3R method improved students’ reading comprehension skills. This research utilized a quantitative method with classroom action research design, with 21 students from Grade VII C of MTs Ma’arif NU 1 Ajibarang as the sample. The study was conducted in two cycles to observed and measured the students’ progress. The research instruments were classroom observations and test. The data from observation used to answer research questions about how the implementation of SQ3R method improved students’ reading comprehension skills. The result of observation showed that students actively asked the terms they did not know, discussed vocabulary that they found and concluding the content of the text. This reflected that they are enthusiastic and interested in implementing the SQ3R method in the class. From the test result showed that the students’ reading comprehension skill after using the SQ3R method improved their score to 18.73% from the mean pre-test 59.48 to the mean post-test I 70.62. In addition, the mean score of second post-test further improved to 86.05, with a 21.85% increase from the first post-test to the second post-test. Furthermore, the results of significance value were 0.000 > 0.05, it means that the students’ reading comprehension skills using the SQ3R method significantly improved. In other words, alternative hypothesis (Ha) was accepted while the null hypothesis (Ho) was rejected. In conclusion, the implementation of the SQ3R method significantly enhanced students’ reading comprehension skills. The researcher suggested the teacher and students to use the SQ3R method to teach and improve students’ reading comprehension skills. Other researchers could also use this research as the guidance and reference to conduct the future research.